Decellularized esophageal tubular scaffold microperforated by quantum molecular resonance technology and seeded with mesenchymal stromal cells for tissue engineering esophageal regeneration - Marzaro, Maurizio; Pozzato, Gianantonio; Tedesco, Stefano; Algeri, Mattia; Pozzato, Alessandro; Tomao, Luigi; Montano, Ilaria; Torroni, Filippo; Balassone, Valerio; Contini, Anna Chiara Iolanda; Guerra, Luciano; D’Angelo, Tommaso; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Increasing the number of seeded cells inside natural decellularised esophageal scaffolds for tissue engineering reconstruction and improving their tridimensional (3D) distribution remains an issue because of their thick connective texture. We report a new prototype of a pig-derived acellular tubular esophageal scaffold treated with the patented Quantum Molecular Resonance® (QMR) technology with an original micro perforation technique. This procedure produced a regular thick microchannel web inside the connective tissue, allowing a diffuse 3D mesenchymal stromal cells culture to spread. At the same time, the resulting scaffold strictly reproduced the original esophagus with the same shape, layers and thickness, also acquiring some of the tensive properties of an artificial scaffold. We had favourable results from the experimental implantation on a large animal-based model with the regeneration of all the scaffold layers resembling the original esophageal wall. Based on these results, we believe that a natural decellularised esophageal scaffold microperforated by QMR treatment would represent a good opportunity for esophageal regeneration for all the patients that need an esophageal substitution.